Status Hak Milik Atas Tanah Fasilitas Umum Di Atas Permukiman - Jumiati, Jumiati; Aswari, Aan; Zulkifli Muhdar, Muhammad (Qawanin Jurnal Ilmu Hukum, 2022)
ABSTRAC This study examines the application of the law to the regulation regarding the procedures for the delivery of public facilities and social facilities in settlements inMakassar City and the status of certificates of ownership of land for public facilitiesabove settlements. This research is a normative-empirical legal research obtainedfrom field studies and literature related to the problem. The type of data used is Primary, which is obtained from field studies, by analyzing a legal problem through facts and questionnaires and secondary, namely legal data that is closely related to primary legal materials that can help analyze and understand primary legal data. The government has regulated the basics and provisions for the control, ownership, use and utilization of agrarian resources contained in Law Number 5 of 1960 concerning Basic Regulations on Agrarian Principles. The law also includes basic principles and provisions, rights to land, water and space as well as land registration, criminal and transitional regulations. The results show that the regulation regarding the procedure for the delivery of public facilities and social facilities in settlements in Makassar City isin the Makassar City Regional Regulation Number 9 of 2011 concerning Provision andDelivery of Infrastructure, Facilities, Utilities in Industrial, Trade, Housing and Settlement Areas specifically funds in general. regulated in the Minister of Home Affairs Regulation Number 9 of 2009 concerning Guidelines for the Delivery of Housing and Settlement Infrastructure, Facilities, and Utilities in the Regions. Regarding the issue of the status of the certificate of property rights above public and social facilities, it must be resolved fairly according to the legislation. ABSTRAK Kajian ini mengkaji penerapan undang-undang terhadap pengaturan mengenai tata cara penyerahan fasilitas umum dan fasilitas sosial pada permukiman di Kota Makassar dan status sertifikat hak milik atas tanah fasilitas umum di atas permukiman. Penelitian ini merupakan penelitian hukum normatif-empiris yang di peroleh dari studi lapangan dan literatur yang berkaitan dengan masalah. Jenis data yang di gunakan adalah primer, yang di peroleh dari lapangan dengan menganalisis suatu masalah hukum melalui fakta fakta dan kuesioner dan sekunder ,yaitu data hukum yang erat kaitannya dengan bahan hukumprimer yang dapat membantu menganalisis dan memahami data hukum primer. pemerintah telah mengatur tentang dasar dan ketentuan mengenail penguasaan, pemilikan penggunaan dan pemanfaatan sumber daya agrariya yang tertuangdalam Undang-Undang Nomor 5 Tahun 1960 tentang peraturan Dasar Pokok-PokokAgraria. Undang-Undang tersebut juga mencakup prinsip dan ketentuan dasar ,hak atas tanah, air dan ruang angkasa serta pendaftaran tanah,peraturan pidana dan transisi. Hasil penelitian menunjukan bahwa pengaturan mengenai tata cara pemberian fasilitas umum dan fasilitas sosial pada permukiman di Kota Makassar terdapat dalam peraturan Daerah Kota Makassar Nomor 9 Tahun 2011 tentang penyediaan dan penyediaan prasaran, saranautulitas perumahan dan permukiman di Daerah. Soal Status Sertifikat hak milik di atas fasilitas umum dan sosial ,harus di selesaikan secara adil sesuai peraturan perundang-undangan.